Virulence of Emerging Arthrotropic Avian Reoviruses Correlates With Their Ability to Activate and Traffic Interferon-γ Producing Cytotoxic CD8+ T Cells Into Gastrocnemius Tendon - Ayalew, Lisanework E.; Ahmed, Khawaja Ashfaque; Popowich, Shelly; Lockerbie, Betty-Chow; Gupta, Ashish; Tikoo, Suresh K.; Ojkic, Davor; Gomis, Susantha (Frontiers in Microbiology, 2022)
Newly emerging arthrotropic avian reoviruses (ARVs) are genetically divergent, antigenically heterogeneous, and economically costly. Nevertheless, the mechanism of emerging ARV-induced disease pathogenesis and potential differences in virulence between virus genotypes have not been adequately addressed. In this study, the life cycle of ARV, including the formation of cytoplasmic ARV neo-organelles, paracrystalline structures, and virus release mechanisms, were characterized in the infected host cell by transmission electron microscopy (TEM). In addition, progressive changes in the structure of infected cells were investigated by time-lapse and field emission scanning electron (FE-SE) microscopy. ARVs from the four genotypic cluster groups included in the study caused gross and microscopic lesions in the infected birds. Marked infiltration of T cells, CD4+ and CD8+ T lymphocytes were observed in ARV infected tendon tissues starting day 3 post-infection. The ARV variant from genotype cluster-2 triggered significantly high trafficking of IFN- producing CD8+ T lymphocytes in tendon tissues and concomitantly showed high morbidity and severe disease manifestations. In contrast, the ARV variant from genotype cluster-4 was less virulent, caused milder disease, and accompanied less infiltration of IFN- producing CD8+ T cells. Interestingly, when we blunted antiviral immune responses using clodronate liposomes (which depletes antigen-presenting cells) or cyclosporin (which inhibits cytokine production that regulates T-cell proliferation), significantly lower IFN- producing CD8+ T cells infiltrated into tendon tissues, resulting in reduced tendon tissues apoptosis and milder disease manifestations. In summary, these data suggest that the degree of ARV virulence and tenosynovitis/arthritis are potentially directly associated with the ability of the virus to traffic massive infiltration of cytotoxic CD8+ T cells into the infected tissues. Moreover, the ability to traffic cytotoxic CD8+ T cells into infected tendon tissues and the severity of tenosynovitis differ between variants from different ARV genotype cluster groups. However, more than one virus isolate per genotype group needs to be tested to further confirm the association of pathogenicity with genotype. These findings can be used to further examine the interaction of viral and cellular pathways which are essential for the pathogenesis of the disease at the molecular level and to develop effective disease control strategies.